Tratamento fisioterapêutico para indivíduos com a doença de Charcot-Marie-Tooth tipo 1 : elaboração e aplicação de um protocolo - Cajueiro, Catarina Andrade Garcez (2018)
Charcot-Marie-Tooth disease (CMT) is a hereditary polyneuropathy that affects sensitive and motor fibers and has a prevalence of 1: 2500. The main clinical manifestations are atrophy and muscular weakness associated with reduced sensitivity, loss of tendon reflexes and impairment of proprioception. The two most frequent forms are CMT1, demyelinating and CMT2, caused by axonal degeneration. The literature data indicate that individuals with CMT disease present with impairment of strength, joint amplitude, balance and functionality. The aim of this study was to develop a protocol for specific physiotherapeutic treatment for individuals with Charcot-Marie-Tooth disease type 1. Material and Methods: A pilot, open-label, almost-experimental clinical trial was conducted by anamnesis, kinetic evaluation-functional and application of an experimental protocol of physiotherapeutic intervention (PECMT) in individuals with CMT1 disease belonging to the same family in the municipality of Pedrinhas / Sergipe / Brazil. The sample consisted of seven adult individuals with CMT1 during 24 sessions of physical therapy. After the implementation of the PECMT program, the patients began to be guided to the realization of a home-oriented exercise program (PDCMT). All patients were evaluated at an initial time (AV1), at the 8th week when they closed the PECMT (AV2) and after six months after the end of the home treatment (PDCMT) (AV3). The muscular strength was evaluated through a manual dynamometer, the ankle range of motion was measured through the fleximeter, the balance through the footwork stabilometer and the Berg balance scale. The functional evaluation was measured by the Timed Up Go (TUG) test. Results: There was a statistically significant difference between AV1 and AV2 for force in all ankle muscles (dorsiflexors: p = 0.0004, plantar flexors: p = 0, 0138, inverters: p = 0.0070, eversores: p = 0.0048 ); knee flexors (p = 0.0062), extensors (0.0061) and abductors (p = 0.0254) of the hip; (P = 0.1990, p = 0.045, p = 0.374) for the VCoP parameters (Velocity of the Pressure Oscillation Center) of the stabilometry in the anteroposterior direction for open and closed eyes respectively (p = 0.1990; for the Berg test (p = 0.0216) and TUG (p = 0.0090). Regarding PDCMT, the TUG (p = 0.0140) showed an increase in the test execution time when compared to the PECMT. The Berg balance scale (p = 0.0544) maintained balance when compared to PECMT. Conclusion: individuals with CMT1 who underwent a specific physiotherapy program demonstrated significant gains in muscle strength, range of motion of the ankle joint and improved performance in functional tests. Guided home-based exercises do not present as satisfactory results as those performed under professional supervision.